Biodiversity and natural product drug discovery - Chulabhorn Mahidol (2018)
The threat to biodiversity through the destruction of terrestrial and marine ecosystems coupled with the urgent need to find novel, new chemotherapeutic agents as well as active chemotypes as leads for effective drug development, make natural products research in drug discovery and development a top priority. The paper will highlight the research of selected natural products aiming at the discovery of therapeutic agents from Thai plants. Attention will be focussed on selected plants that possess cytotoxic properties.